Intraluminar testicular colonization and differentiation of the inner cell mass in mice (Mus Musculus) - Acosta, Láyonal (2011)
Primordial germ cells (PGC`s) are transplanted to testicle of other individual of the same species, they colonize the lumen of the seminiferous tubules, seeking a niche to differentiate into sperm. Our objective was to evaluate the intraluminal colonization of a suspension of cells in the inner cell mass (IMC`s) of blastocysts obtained from mice, using a novel technique. It was transplanted a suspension of ICM by mean of inmunosurgery into the rete testis of recipient animals which were previously treated with cyclophosphamide to reduce their own spermatogenesis. We confirmed the presence of intraluminal minitubules in 2 of 100 seminiferous tubules, demonstrating that transplantation of a suspension of cells from the inner cell mass can colonize the seminiferous tubules and also maintain a synchronously xenogenic spermatogenesis with the receiver.